EFFECT OF SEEDS PRIMING AND FOLIAR APPLICATION WITH SEAWEED EXTRACT ON SOME YIELD TRAITS OF TWO SUNFLOWER CULTIVAR - Abbas, Hawraa; Saudi , A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A field experiment was conducted during tow spring seasons of 2022 and 2023 in the experimental fields of the College of Agricultural Engineering Sciences - University of Baghdad using RCBD design according to factorial experiments with three replicates and three factors including sunflower cultivars (Ishaqi 1 and Ishaqi 2). The second factor included seeds priming with seaweed extract (Acadian) concentrations (0, 3, and 4 mg L-1), in addition to with, foliar application of seaweed extract at the aforementioned concentrations. The results showed the significant superiority of the Ishaqi2 cultivar in all studied traits for both seasons. The treatment with priming and foliar application with Acadian at a concentration 4 mg L-1 showed superiority in most of the studied traits. In the first season, the effects of the two-way and three-way interactions of the study factors varied in their impact, but the interaction between the Ishaqi2 cultivar, priming at a concentration 3 mg L-1, and foliar application at a concentration 4 mg L-1 was the most prominent in most of the studied traits. To achieve the best increase in sunflower yield.